Peace Spirituality Through Interreligious Engagement - Imanuel Geovasky (Journal of Ethics in Higher Education, 2024)
Historically, Yogyakarta had enjoyed the reputation of being a bastion of interreligious tolerance in Indonesia. Still, a growing spate of events that were manifestations of religious intolerance calls for a rethinking of that narrative. This paper examines public space civility, peace spirituality, and interreligious engagement in Yogyakarta. Through a quantitative survey approach, it is found that there is a statistically significant positive relationship between positive public space civility and peace spirituality. Apart from the positive correlations of public behaviour and peace spirituality, there is also a theory-practice gap, in that most measures seemed to make the Muslim and Christian participants alike appear very insecure. The current study extends earlier research and underlines how grassroots interreligious engagement can stand in front in peace-making, enhancing spirituality, and religious tolerance.